Digital Marketing Strategy for MSMEs to Increase Competitiveness of Local Products: Strategi Pemasaran Digital UMKM untuk Meningkatkan Daya Saing Produk Lokal (Indonesian Journal of Cultural and Community Development, 2024)
General background in the current digital era, small and medium enterprises (MSMEs) are a vital component of local economic development, particularly in rural areas. Specific background MSMEs producing local products such as bags and suitcases are prominent in certain regions, but face significant marketing challenges. Knowledge gap: However, few studies have explored the application of digital marketing strategies to improve the competitiveness of local MSME products.This study aims to analyze the application of digital marketing as a marketing strategy for local village products to increase the competitiveness of MSMEs using a SWOT analysis approach. The results show that MSMEs need strong government and institutional support to overcome market barriers and adopt advanced marketing techniques. The findings emphasize the importance of training and mentoring programs to enhance technical and managerial skills, as well as the introduction of new technology. Additionally, creating a community of craftsmen and entrepreneurs can foster knowledge-sharing and expand business networks, contributing positively to the competitiveness of local products. Novelty the study introduces a comprehensive approach that combines digital marketing and community building, which has not been extensively studied in the context of rural MSMEs. The implications of this research suggest that by leveraging digital platforms and forming supportive networks, MSMEs can increase their market reach and competitiveness, contributing significantly to local economic growth.Highlights:• MSMEs require digital marketing strategies to boost product competitiveness.• Government support and training are crucial for overcoming market challenges.• Community-building among craftsmen enhances business networks and knowledge-sharing.Keywords: MSMEs, Digital Marketing, Competitiveness, Local Products, SWOT